2022
DOI: 10.1111/iej.13744
|View full text |Cite|
|
Sign up to set email alerts
|

Micro‐CT assessment of gap‐containing areas along the gutta‐percha‐sealer interface in oval‐shaped canals

Abstract: Aim: To assess the interfacial adaptation (gap-containing areas) of two root canal sealers (EndoSequence BC Sealer and AH Plus) to a conventional gutta-percha (GP) cone (GP-sealer interface) in oval-shaped canals filled using the single cone technique.Methodology: Sixteen teeth with oval-shaped canals were selected, scanned in a micro-computed tomographic device, and pair-matched according to the volume, aspect ratio and configuration of root canals. Root canals were then sequentially prepared with WaveOne Gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…ES showed a similar tendency, although its setting time was within the ISO standard. The heat-induced increase in the film thickness of AHB indicates that the advantages of warm vertical compaction, such as a thinner sealer layer owing to the higher gutta-percha-filled rate [5] and decreased porosity [46], may not be fully exploited.…”
Section: Discussionmentioning
confidence: 99%
“…ES showed a similar tendency, although its setting time was within the ISO standard. The heat-induced increase in the film thickness of AHB indicates that the advantages of warm vertical compaction, such as a thinner sealer layer owing to the higher gutta-percha-filled rate [5] and decreased porosity [46], may not be fully exploited.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this finding is that lowering tri- and di-calcium silicate levels decreases the expansion ability of TCS. A second option is that the change in sealer composition might have increased the gaps formation in the interphase GP cone – sealer, as was demonstrated by a recent work [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent micro-ct analysis [ 11 ] aimed to assess adaptation of epoxy sealer and a TCS sealer to GP cone by means of gap formation along the specimens. The authors concluded that while no specimens exhibited a completely gap-free area along the entire interface of GP-sealer, oval canals filled with AH Plus demonstrated fewer gaps compared to those filled with EndoSequence BC Sealer.…”
Section: Objectivementioning
confidence: 99%
“…Therefore, it is questionable whether these sealers are suitable in inflamed areas with a low pH value [49][50][51]. Other drawbacks of CSSs are that they might cause tooth discoloration [52,53], especially due to contamination with blood [54]; GP-sealer interfaces are more frequent in CSSs [55]. Moreover, they remain moderately cytotoxic over six weeks [41].…”
Section: Calcium Silicate-based Sealers (Csss)mentioning
confidence: 99%